Respostas

A melhor resposta!
2014-07-11T19:44:13-03:00
A) 3x² - 6x - 24 = 0, p/ a = 3, b = -6 e c = -24
x1 + x2 = -b/a = 6/3 = 2 
x1.x2 = c/a = -24/3 = -8
..........
b) 6x² - 20x + 6 = 0, p/ a = 6, b = -20 e c = 6
x1 + x2 = -b/a = 20/6 = 10/3
x1.x2 = c/a = 6/6 = 1
..........
c) 2x² + 9x + 4 = 0, p/ a = 2, b = 9 e c = 4
x1 + x2 = -b/a = -9/2
x1.x2 = c/a = 4/2 = 2
..........
d) -1/3 - 2x + 9 = 0, p/ a = -1/3, b = -2 e c = 9
x1 + x2 = -b/a = 2/(-1/3) = 2.(-3) = -6
x1.x2 = c/a = 9 / 1/3 = 9 . 3 = 27

2 5 2